FORMATION, HYDROLOGICAL REGIME AND DYNAMICS OF WATER RESOURCES IN THE SHERABAD RIVER BASIN UNDER CLIMATE CHANGE - Karimov, Ilhom Esonovich; Mustayev, Kurbonmurod Rakhmonovich (SCIENCE and SOCIETY, 2026)
This article analyzes the conditions for water resource formation in the Sherabad River basin, the structure of the hydrographic network, flow indicators at gauging stations, and the seasonal distribution of flow in years with different water levels as the main factors determining the river regime. The results show that the majority of annual flow occurs in spring and the first half of summer; the share of flow in April-June is 55.1% in years with average water levels. In years with low and very low water levels, summer flow decreases, while the share of the autumn-winter period increases. It has been analyzed that this situation increases the risk of water shortages for irrigated agriculture in the second half of the growing season.
Keywords: Sherabad River; water resources; hydrological regime; climate variability; seasonal runoff; water shortages; irrigation